PERANAN ANALISIS MANAJEMEN KREDIT UNTUK MENURUNKAN TERJADINYA KREDIT BERMASALAH - Sri Handayani; Mimi Kurnia Nengsih (Unib Press Universitas Bengkulu, 2019)
This study aims to identify and analyze credit management, the cause of bad credit, and handling loan problems in banking. This research uses quantitative methods, and the data used are secondary. The data used is based on the application of credit management and credit collectibility data, the level of Capital Adequacy Ratio (CAR), Non-Performing Loans (NPL), loan limits, and Loan to Deposit Ratio (LDR). The results of this study indicate that Bengkulu Branch BTPN has carried out the stages of credit management appropriately. The findings in this study explain that the causes of bad credit are customers who have family problems, business failures, and unexpected things. The handling of problem loans is done by rescheduling, reconditioning, restructuring, and handing over collateral to BTPN KC Bank Bengkulu.